PHYSICAL PROPERTIES OF SECOND GENERATION BIOETHANOL FUEL MADE FROM BREM WASTE - Indah Puspitasari; Nanang Romandoni (Jurnal Poli-Teknologi, 2018)
ABSTRACTSecond generation bioethanol fuels are made from the vegetable material containing cellulose and lignin which is generally a solid agro-industrial waste biomass. Biomass waste has a considerable amount in Indonesia. One of them is waste from the brem food processing industry in Caruban Madiun. Bioethanol is potential to be utilized as motor vehicle fuel with a requirement of 99.5% purity and has properties corresponding to the standard of denatured bioethanol for gasohol. This research was conducted by experimental method, which is making second generation bioethanol fuel from the waste of brem in laboratory scale. The initial stage is hydrolysis and then fermentation process by using saccharomyces cerevisiae yeast with a variation of fermentation length, yeast weight, and water volume. The next process is distillation stage one, distillation of stratum, and dehydration by adding salt and silica gel. The optimal bioethanol is then blended with pertalite and tested for octane value characteristics.The results of this study obtained the best comparison of 250 grams of brem waste, 1250 ml of water, 10 grams of yeast tape, and 5 days of fermentation time with 93% alcohol content. From the alcohol content, the characteristics of the mixture of pertalite and bioethanol were obtained. The result of octane value was E5 which was 100.8; E10 is 101.3; and E15 equal to 106.8. The more a mixture of bioethanol with pertalite, the greater the octane value.Keywords: second generation bioethanol, alternative fuels, brem waste, standard of denatured bioethanol for gasoholABSTRAKBioetanol generasi kedua adalah bioetanol dari bahan nabati yang mengandung selulosa dan lignin yang umumnya merupakan biomassa limbah padat agroindustri. Limbah biomassa mempunyai jumlah cukup besar di Indonesia. Salah satunya adalah limbah dari industri pengolahan makanan brem di Caruban Madiun. Bioetanol potensial untuk dimanfaatkan sebagai bahan bakar kendaraan bermotor dengan syarat memiliki kadar kemurnian 99,5% dan mempunyai properties yang sesuai dengan standart mutu bioetanol terdenaturasi untuk gasohol. Penelitian ini dilakukan dengan metode eksperimental, yaitu membuat bioetanol generasi kedua dari limbah ampas brem skala laboratorium. Tahap awal adalah hidrolisa, kemudian fermentasi dengan menggunakan ragi Saccharomyces cereviceae dengan variasi penelitian yaitu lama fermentasi, berat ragi dan volume air. Proses berikutnya adalah distilasi dan distilasi bertingkat serta dehidrasi dengan menambahkan garam dan silica gel. Bioetanol paling optimal selanjutnya diblending dengan pertalite dan diuji karakteristik nilai oktan. Hasil dari penelitian ini didapatkan perbandingan terbaik yaitu 250 gr limbah ampas brem, 1250 ml air, 10 gr ragi tape, dan lama waktu fermentasi 5 hari dengan kadar alkohol 93%. Dari kadar alkohol tersebut dilakukan uji karakteristik campuran pertalite dan bioethanol didapat hasil nilai oktan yaitu E5 sebesar 100,8; E10 sebesar 101,3; dan E15 sebesar 106,8. Semakin banyak campuran bioetanol dengan pertalite maka nilai oktan semakin besar.Kata kunci : bioetanol generasi kedua, bahan bakar alternatif, limbah ampas brem